Poczucie „Inności” u osób niewidomych i osób z resztkami wzroku w sferze funkcjonowania psychicznego, fizycznego i emocjonalnego - Zaorska, Marzenna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The articles main subject are considerations on the topic of the sense of “being different” that young blind, and nearly-blind people feel, in spheres of life such as physical and psychical. The article also highlights the dependencies of the feeling of “being different” on characteristics like age, sex, place of residence, marital status, the state of vision in both the left or the right eye, additional disabilities, other physical limitations, level of disability, period of vision damage, work or educational activity, type of educational activity, acceptance level of the disabled person in his/hers family, personal acceptance of disability, preferred ways of self-improvement, additional rehabilitation needs. Also the hypothetical directions of needed actions are given in the article.